Actual problems in the process of regulating prosecutor’s inspection over the execution of laws and the ways of eliminating them - KOMILOV Avazbek Bokijonovich (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article explores actual problems in the process of regulating prosecutor's inspection over the execution of laws and the ways of eliminating them. The author argues that developing and refining the legal basis for prosecutorial inspections is of significant importance today, and the issue remains highly relevant. Uzbekistan's national legislation, along with the internal regulatory documents of its prosecutorial bodies, is in urgent need of comprehensive improvement in this area. Presently, the legal regulation of prosecutorial inspections is still in its early stages. By adjusting the process for initiating and conducting prosecutorial inspections – through the Law of the Republic of Uzbekistan “On the Prosecutor’s Office” and the directives of the Prosecutor General – several key results can be achieved: a fundamental transformation in how prosecutors approach inspections; the prevention of unjustified interference in the operations of inspected entities; the protection of the rights and interests of those entities; the establishment of a formal right to appeal prosecutorial actions and decisions; and, importantly, the strengthening of personal responsibility and accountability among prosecutors regarding inspection-related decisions. Moreover, such legal regulation would shift the focus of inspections from quantity to quality, thereby significantly enhancing their overall efficiency and impact. To address these challenges, the author presents a set of scientifically grounded and practically applicable proposals and recommendations.